Analisis Kohesi Leksikal dalam Wacana Berita Olahraga Majalah Panjebar Semangat Tahun 2019 - Conix Faqihana Dini; Atikah Anindyarini; Rahmat Rahmat (Universitas Sebelas Maret, 2022)
This research discusses the lexical cohesion analysis contained in the Panjebar Semangat magazine sportcasts in 2019. The aimed of this research is to describe lexical cohesion of the sportscast Panjebar Semangat magazine in 2019. Type of this study is qualitative descriptive research. Source of data in this research consisted of 12 news discourses in the Panjebar Semangat magazines in 2019, journals and references books. Purposive sampling techniques was used as a sampling method. The news discourse under study represented the news of Panjebar Semangat magazine which was published in January-December 2019. The results of this study are lexical cohesion which includes repetition, synonymy, antonym, collocation, hyponym, and equivalence. Lexical cohesion data found after analysed were 147 data. Repetition is the most data found in this study.